Unusual binding interactions in PDZ domain crystal structures help explain binding mechanisms. - Elkins, J; Gileadi, C; Shrestha, L; Phillips, C; Wang, J; Muniz, J; Doyle, D (2010)
PDZ domains most commonly bind the C-terminus of their protein targets. Typically the C-terminal four residues of the protein target are considered as the binding motif, particularly the C-terminal residue (P0) and third-last residue (P-2) that form the major contacts with the PDZ domain's "binding groove". We solved crystal structures of seven human PDZ domains, including five of the seven PDLIM family members. The structures of GRASP, PDLIM2, PDLIM5, and PDLIM7 show a binding mode with only the C-terminal P0 residue bound in the binding groove. Importantly, in some cases, the P-2 residue formed interactions outside of the binding groove, providing insight into the influence of residues remote from the binding groove on selectivity. In the GRASP structure, we observed both canonical and noncanonical binding in the two molecules present in the asymmetric unit making a direct comparison of these binding modes possible. In addition, structures of the PDZ domains from PDLIM1 and PDLIM4 also presented here allow comparison with canonical binding for the PDLIM PDZ domain family. Although influenced by crystal packing arrangements, the structures nevertheless show that changes in the positions of PDZ domain side-chains and the alpha B helix allow noncanonical binding interactions. These interactions may be indicative of intermediate states between unbound and fully bound PDZ domain and target protein. The noncanonical "perpendicular" binding observed potentially represents the general form of a kinetic intermediate. Comparison with canonical binding suggests that the rearrangement during binding involves both the PDZ domain and its ligand.